Tuberculosis drug streptomycin as a potential cancer therapeutic: inhibition of miR-21 function by directly targeting its precursor - Bose, Debojit; Jayaraj, Gopal Gunanathan; Suryawanshi, Hemant; Agarwala, Prachi; Pore, Subrata Kumar; Banerjee, Rajkumar; Maiti, Souvik (Angewandte Chemie-International Edition, 2012)
Keywords: Apoptosis; drug discovery; Gene expression; inhibitors; RNA

Pharmacore maping based on docking, ADME/toxicity, virtual screening on 3,5-dimethyl-1,3,4-hexanetriol and dodecanoic acid derivates for anticancer inhibitors - Prakash, Palanisamy; Vijayasarathi, Durairaj; Selvam, Kuppusamy; Karthi, Sengodan; Manivasagaperumal, Rengarajan (Journal of Biomolecular Structure & Dynamics, 2021)
Plants produced natural generating products play a significant role in drug discovery of new bioactive compounds and these are used for advancement of innovative curative drugs for specific target health diseases. In this study Docking and ADME/T virtual screening method are apply for in drug discovery and can be divided into ligand- and target structure-based. The aim of this study was to analyze theDecalepis hamiltoniiisolated compounds by using the evaluation of molecular docking and virtual screening of anticancer drugs. MOE docking ADME/Toxicity and virtual screening approaches. A docking energy -12.97 kcal/mol; -9.93- kcal/mol on cancer responsible protein was targeted. Further, the compounds were filtered through the rule of five, ADME/Toxicity risk and synthetic accessibility. The active compound were then docked to recognize the possible target binding pocket to obtain a set of a ligand poses and to prioritize the predicted active compounds. The scrutinize compounds, as well as their metabolites were evaluated for different pharmacokinetics parameter such as ADME/Toxicity. Therefore, the result shows that a large number of compounds were found to be ADME/toxicity positive to be a positive drug molecule against cancer, selected compounds under study satisfies parameters for ADME and Toxicity properties. The present study demonstrate to identifying the novel structures which are having similar structural feature with like activity with respect to the compounds 3,5-Dimethyl-1,3,4-Hexanetriol and Dodecanoic acid that are shown best binding energy with the receptors 4igk and 4b3z respectively. This study may provide significant clues for discovery novel drug inhibitors for cancer properties.
Keywords: ADME; Decalepis hamiltonii; docking; drug discovery; Toxicity; virtual screening

On the use of electronegativity and electron affinity based pseudo-molecular field descriptors in developing correlations for quantitative structure-activity relationship modeling of drug activities - Kunde, Pushkar D.; Ramkumar, Sudha; Kamble, Sanjay P.; RaviKumar, Ameeta; Kulkarni, Bhaskar D.; Kumar, V. Ravi (Chemical Biology & Drug Design, 2021)
For quantitative structure-activity relationship (QSAR) modeling in ligand-based drug discovery programs, pseudo-molecular field (PMF) descriptors using intrinsic atomic properties, namely, electronegativity and electron affinity are studied. In combination with partial least squares analysis and Procrustes transformation, these PMF descriptors were employed successfully to develop correlations that predict the activities of target protein inhibitors involved in various diseases (cancer, neurodegenerative disorders, HIV, and malaria). The results show that the present QSAR approach is competitive to existing QSAR models. In order to demonstrate the use of this algorithm, we present results of screening naturally occurring molecules with unknown bioactivities. The pIC(50) predictions can screen molecules that have desirable activity before assessment by docking studies.
Keywords: drug discovery; electron affinity; Electronegativity; molecular field descriptors; partial least squares; QSAR

Novel pyrazole derivatives as inhibitors of Leishmania donovani: an integrated approach combining in vitro analysis and mechanistic insights - Kumari, Diksha; Kour, Jaspreet; Kumar, Anuj; Sangral, Monica; Singh, Shashank K.; Sawant, Sanghapal D.; Singh, Kuljit (Bioorganic Chemistry, 2025)
Leishmaniasis is a neglected tropical disease that continues to be a global public health problem, leading to a disastrous impact on poor rural people. The present therapeutic arsenal faces the limitations of drug resistance and toxicity concerns, raising a great need to identify novel chemical scaffolds that are potent, non-toxic, and cost-effective. Heterocycles comprise a distinctive class of molecules exhibiting a wide array of physical, chemical, and biological characteristics and occupy a prominent position in pharmaceutical applications. In the present study, we aimed to investigate three series of pyrazole derivatives synthesized previously by our group for their anti-leishmanial potential against Leishmania donovani parasites. Primarily, 29 compounds were evaluated using an Alamar blue dye-based assay for their inhibitory potency, out of which six molecules (4a, 4b, 4c, 4j, 7a, and 7d) were active with >50 % growth inhibition at a 50 mu M dose. Among them, three molecules (4b, 4j, and 7d) showed remarkable leishmanicidal potency with 50 % inhibitory concentration (IC50) in the range of 5 to 13 mu M. Toxicity analysis revealed that the potential hit (4j) represented a promising cytocompatibility profile along with noteworthy activity against L. donovani intracellular amastigotes. Furthermore, the in-depth mechanistic evaluation using scanning electron microscopy, reactive oxygen species (ROS) generation, mitochondrial membrane potential (Delta Psi m) determination, ATP quantification, cell cycle analysis, and lipid accumulation assay confirms the inhibitory potential of compound 4j. Thus, the present study represents pyrazole derivatives as a potential scaffold for the development of novel chemotherapeutics against leishmaniasis.
Keywords: Cell death; drug discovery; FACS analysis; leishmaniasis; Pyrazole derivatives; Reactive Oxygen Species (ROS); scanning electron microscopy

Ready access to benzodiazocines from tryptamines: a druggable scaffold toward antiviral agents - Saranya, N. Sathya Sai; Choudhury, Rahul; Routholla, Ganesh; Supekar, Prathmesh R.; R, Nandhakumaar; Martin, Alna Kuriyickal; Muruganandham, Renuga Devi; Kumar, Bokara Kiran; Reddy, D. Srinivasa (ACS Medicinal Chemistry Letters, 2025)
Herein we report the first synthesis of the proposed structure of a benzodiazocine natural product, peganutonin A. Considering the druggable nature of benzodiazocine and its limited exploration in the field of medicinal chemistry, we generalized the approach and created a library of compounds useful for various biological activities. Key steps in present approach include tryptamine cyclization facilitated by tert-butyl hypochlorite and cleavage of the fused indole ring using ozonolysis. Preliminary screening of the synthesized compounds resulted in potent antiviral compounds against the SARS-CoV-2 virus.
Keywords: Benzodiazocine; drug discovery; Indole cleavage; Lipinski's rule of Five; SARS-CoV-2 inhibition; Tryptamine